Big yellow taxi, or, unhealthy terms of trade? - Dorothy Broom (Elsevier, 2003)
Abstract International trade agreements, including the General Agreement on Trade in Services, are central elements of globalisation. These agreements are likely to have significant implications for population health in rich nations such as Australia as well as in the developing world. But the technical language of the legal agreements and the comparative secrecy of the negotiations and approval procedures make it difficult for most people to be adequately informed about them. Australian public health academics and practitioners must become better informed and more pro‐active in their approach to 'free trade' if Australia's public health infrastructure is to be protected from potential legal erosion.